The Power of Social Media - Mohd Zaki, Ahmad (2020)
Today’s technologies, such as social media, mobile, cloud, and big data, bring people closer together. Social media has become extremely effective and almost a costless tool in reaching mass audiences for any purposes. Social media has also become a tool for business people to promote their products, and for politicians, social media has become a tool to carry out their political propagandas. Millions of users from all over the world can communicate with each other in various platforms.